Computational Fluid Dynamics (CFD) analysis of a flow straightener for a heater chimney - Bacchi, Federico (2013)
This work presents a numerical analysis by means of computational fluid dynamics (CFD) of the flow within and outside a chimney of low length/diameter ratio with a lateral inlet for combustion gases. A partially blocked gases entrance and cyclonic flow present in the chimney in its actual configuration prevent the system to fulfill particulate flow control regulations, in particular concerning the velocity vector inclination in the control plane where monitoring is carried out. A flow straightener device is proposed which reduces, in the numerical simulations, the inclination of streamlines in the flow control plane from more than 35 degrees to less than 5 degrees, meeting the criteria stated in environmental regulations for particle emission control, without introducing excessive pressure losses in the flow. Results of the analysis include the flow configuration, velocity and pressure distributions and helicity distribution, the latter as a measure of the intensity of cyclonic flow.